EFFECT OF HORMONAL PROTOCOLS ON BLOOD SERUM PROFILE IN POSTPARTUM ANOESTRUS BUFFALOES DURING NONBREEDING SEASON - PATIL, A D; SAHATPURE, S K; KORDE, J P; PATIL, D V (The Indian Journal of Animal Reproduction, 2022)
The study was conducted on 40 postpartum anoestrus buffaloes during non-breeding season. The selectedanimals were divided into 4 equal groups. Group I was treated with standard Ovsynch + CIRD protocol, Group II withCIDR alone, and Group III was administered with Ovsynch protocol alone, all with FTAI on day 10, while Group IVserved as untreated control. Blood samples were collected on day 0 (initial), day 7 (day of PG inj.) and on day 10(FTAI) of each protocol for determination of haemato-biochemical profile. The overall mean values of WBCs, RBCs,haemoglobin, plasma glucose, and serum total protein, total cholesterol, calcium and phosphorus were statisticallysimilar on all days in all groups. The serum levels of Cu, Fe and Zn increased significantly (p
Keywords: Hormonal protocol; Haemato-biochemical profile; Anoestrus buffaloes; Non-breeding season